Estudio del nivel de percepción de la atención brindada en la Jefatura de Recaudaciones del GAD Municipal de Loja, periodo 2023 - Cabrera Guamán, Dayana Lisbeth (2024)
This curriculum integration work was carried out with the purpose of evaluating the perception of service quality provided by the Revenue Department of the Municipal GAD of Loja, which is located on Bolívar and José Antonio Eguiguren streets during the 2023 period, considering the perceptions of the people who use service, the knowledge and experience of the Revenue area staff, as well as the physical facilities and infrastructure. To carry out this research project, the general objective was set as "To evaluate the level of perception in the service provided at the Revenue Department of the municipal GAD of Loja, during the 2023 period", and specific objectives were: to describe the current situation of the municipal Revenue Department in the city of Loja, during the 2023 period; to measure quality level of the municipal Revenue Department in the city of Loja, during the 2023 period; and to propose a strategy to improve the services quality at the municipal Revenue Department in the city of Loja. With the purpose of achieve the expected results, Servperf model was applied to effectively assess the quality focused on users’ perspective, which proposes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy, to determine the quality of the service received. The Servperf model was adapted according to the research requirements, which contains a 22-item questionnaire applied to a sample of 384 users who used the revenue service. In addition, it is necessary to mention that the results of this research show that the quality perception in the service provided by the Municipal Revenue Department falls within a moderate quality range. Subsequently, based on the results obtained, a proposal for improving service quality was developed, considering each of the variables involved in this research, which will help address the weaknesses that exist in the Municipal Revenue Department. Furthermore, conclusions, recommendations, and discussion are presented at the end of this research, they will contribute to achieve a high level of quality and, therefore, to improve the performance of the staff in the Revenue Department of the Municipal GAD of Loja.